Estudio de las estrategias del marketing digital y su influencia en la fidelización de los consumidores que realizan compras en supermercados online en Lima Metropolitana - Chamochumbi Muñante, Tatiana Morella (2022)
This study aims to determine how digital marketing strategies influence consumer loyalty who make purchases in online supermarkets in Lima Metropolitana. The type of research is applied and has a quantitative approach. For this reason, for the present study, a virtual survey was carried out on 385 people over 18 years old who reside in Lima and make purchases in online supermarkets. The first chapter presents the formulation of how digital marketing strategies can influence consumer loyalty, also describes objectives, importance of the research and limitations of the study. In the second chapter, antecedents and convenient theoretical bases for the investigation are exposed. Among them, various investigations show that consumers are not satisfied with the online shopping service. In chapter three, the general and specific hypotheses and operationalization of variables under study are presented. Likewise, in chapter four, the calculation of the sample is detailed, as well as the elaboration of research instrument and statistical software that was SPPSS 26, is specified. The fifth chapter shows the results of the application of the survey with their respective graphs. The results indicate that digital marketing strategies: omnichannel, engagement and e-commerce influence the repurchase of online supermarket, that is, they influence loyalty. Finally, conclusions and recommendations for online supermarkets that seek to increase the loyalty of their consumers are explained.